Maximally stationary window design for overlap-add based random vibration synthesis - Damián González; R. López-Valcarce (Mechanical Systems and Signal Processing, 2019)
The accurate synthesis of realistic waveforms conforming to certain speci ca- tions is a fundamental step in random vibration testing. Since real-time imple- mentation of digital signal processing systems for random vibration and noise synthesis necessarily operates frame by frame, the overlap-add (OLA) method, by which frames are windowed and overlapped, is widely used in practice to avoid artifacts at frame boundaries. When a wide-sense stationary random signal is desired, however, the OLA method presents a shortcoming, because the inherent periodicity of the frame-by-frame process unavoidably produces a cyclostationary signal, i.e., its statistics present an undesired periodic behav- ior. We analyze the impact of the window coecients in the cyclostationarity properties of the synthetic process, and then present algorithms for window de- sign with the goal of maximizing a measure of its stationarity, considering both second- and fourth-order statistical properties. The proposed designs are shown to signi cantly improve the stationarity properties when compared to commonly used windows.
Keywords: random vibration